2005
DOI: 10.1002/ijc.21118
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses to DNA mismatch repair enzymes hMSH2 and hPMS1 in patients with pancreatic cancer, dermatomyositis and polymyositis

Abstract: To identify tumor antigens useful for diagnosis and immunotherapy of patients with pancreatic ductal adenocarcinoma, we applied a SEREX approach with a cDNA library made from 5 pancreatic cancer cell lines and sera obtained from 8 patients with pancreatic cancer, and isolated total 32 genes, including 14 previously characterized genes and 18 genes with unknown functions. Among these isolated antigens, serum IgG antibodies for 2 isolated DNA mismatch repair enzymes, Homo sapiens mutS homolog 2 (hMSH2) and Homo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 37 publications
0
15
0
2
Order By: Relevance
“…Further evidence for this model comes from a recent study of antigen expression in pancreatic adenocarcinoma [34 ]. In that study, antibodies to two DNA mismatch repair proteins (polymyositis S1 and MSH2) were found in eight patients with pancreatic adenocarcinoma, and levels of these proteins were noted to be increased in immunohistochemical analysis of affected tissue.…”
Section: Figure 1 Myositis-specific Autoantigen Expression Is Increasmentioning
confidence: 91%
“…Further evidence for this model comes from a recent study of antigen expression in pancreatic adenocarcinoma [34 ]. In that study, antibodies to two DNA mismatch repair proteins (polymyositis S1 and MSH2) were found in eight patients with pancreatic adenocarcinoma, and levels of these proteins were noted to be increased in immunohistochemical analysis of affected tissue.…”
Section: Figure 1 Myositis-specific Autoantigen Expression Is Increasmentioning
confidence: 91%
“…hMLH1 is a common subunit to all three complexes, and its deficiency lead to a sever disease phenotype [12][13][14][15][16][17]. Recent reports have shown that hMLH1 not only physically interacts with other components of MMR but also interacts with other signaling molecules such as BRCA1 [18], PCNA [19], ATM [20], P53 [21,22] and other enzymes such as BLM (DNA helicase) [23], Exo1p [24] and MED1 [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…La DM asociada a malignidad es un sĂ­ndrome paraneoplásico que puede presentarse antes de la enfermedad oncolĂłgica, simultáneamente o meses e incluso años despuĂ©s de la misma. Afecta a individuos de grupos etarios de más de 40 años, incrementándose aĂşn más por encima de los 60 años.Los tumores más frecuentemente asociados son el cáncer de ovario, mama, pulmĂłn, colon, Ăştero, estĂłmago y sĂ­ndromes mieloproliferativos [14][15][16][17][18][19] . Ciertos estudios manifiestan la presencia de antĂ­genos compartidos por cĂ©lulas tumorales y musculares, expresando una respuesta inmune contra el musculo y la piel.…”
Section: Introduccionunclassified
“…Ciertos estudios manifiestan la presencia de antĂ­genos compartidos por cĂ©lulas tumorales y musculares, expresando una respuesta inmune contra el musculo y la piel. El tratamiento de la neoplasia puede mejorar o no las manifestaciones de la DM [14][15][16][17][18][19] . A continuaciĂłn presentamos tres casos de DM asociados a neoplasias.…”
Section: Introduccionunclassified